2021
DOI: 10.1021/acsaem.1c02087
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dye Sensitized Solar Cell and Photocapacitor Performance with Efficient Electrocatalytic SWCNH Assisted Carbon Electrode

Abstract: The present work demonstrates the high photovoltaic power conversion efficiency (PCE) of 11.12% using single wall carbon nanohorn assisted carbon counter electrode based dye sensitized solar cells (DSSCs), which demonstrates a superior PCE compared to that of platinum (9.41%). This superior performance was a motivation to fabricate a dye sensitized solar module (DSSM) consisting of six series connected DSSCs arranged in a bifacial manner toward the application of building integrated photovoltaics. The DSSM dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The combination of solar harvesting and storage in a single device by integrating PV into the SC applications is a relatively new research topic in the energy field. [21][22][23][24][25][26][27][28][29][30] These devices have the advantages of being light-weight, small-sized, and compact when the solar cell is connected as a back electrode to the supercapacitor as a working electrode. On the other hand, semiconducting materials with simultaneous photosensitive and capacitive behaviour can achieve light-harvesting and charge storage.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of solar harvesting and storage in a single device by integrating PV into the SC applications is a relatively new research topic in the energy field. [21][22][23][24][25][26][27][28][29][30] These devices have the advantages of being light-weight, small-sized, and compact when the solar cell is connected as a back electrode to the supercapacitor as a working electrode. On the other hand, semiconducting materials with simultaneous photosensitive and capacitive behaviour can achieve light-harvesting and charge storage.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of improved electron and hole transfer in the charge–discharge process, the 3-T design showed a photocharged voltage under 1 sun of 0.8 V and energy density of 47 μWh cm –2 . Since then, a plethora of materials and configurations have been investigated. , …”
Section: Integration Of Photocapacitorsmentioning
confidence: 99%
“…30 Thereaer, several research works were reported with integrated architectures. [36][37][38] However, the heterostructured photocapacitors are of great interest due to the direct contact between the photoactive and storage materials, making the working electrode itself a light absorber and an energy storage device through an oxidation process. This heterostructured photocapacitor possesses the unique synergistic coupling of photoactive materials and a transition metal sulde to drive the transition metal oxide derived from its sulde to act as a capacitive platform via redox pseudocapacitance under illumination.…”
Section: Photocapacitorsmentioning
confidence: 99%